The fertility show as a field-configuring event: a critical discourse analysis - Cervi, Lucia (2017)
This thesis explores how Field-Configuring Events (FCEs) discursively maintain field legitimacy. It particularly addresses how organisations within the field of fertility treatment employ discourses of the female non-reproductive body at one of the field’s FCEs, the Fertility Show. FCEs are temporally and spatially bounded events where organisations belonging to the same field meet and share collective understandings of issues relevant for field-level activities. Despite being acknowledged as important loci for field configuration and legitimacy (Lampel and Meyer, 2008; Wooten and Hoffman, 2016), FCEs are still relatively understudied phenomena. This research particularly addresses the gap of how discourse is generated and employed at FCEs (Hardy and Maguire, 2010), specifically towards legitimacy. It sits within an academic discussion that sees a number of empirical studies concerned with the discursive analysis of legitimacy (Vaara et al., 2006; Alvesson, 1993; Brown, 1998), but a critical perspective to the analysis of discourse is rarely taken (Vaara et al., 2006; Barros, 2014). The thesis contributes to this discussion by adopting a Critical Discourse Analysis (CDA) approach to unveil discursive strategies of legitimacy employed at the FCE to maintain field legitimacy. As a dynamic and on-going process (Deegan, 2002; Suchman, 1995), legitimacy needs to be maintained (Shocker and Sethi, 1974). Scholars acknowledge that FCEs can work towards field maintenance (Schüssler et al., 2014), however studies that discursively investigate this process and its implications for legitimacy are missing. The importance and peculiarity of FCEs represent a compelling case for analysis, and for empirical and theoretical expansion in this regard. This thesis importantly also focuses on the concept of the body within organisation studies, and zooms in on the female body in particular. With respect to this literature, works so far have mostly analysed the body at work. The study shifts the attention from the body of the worker to the body per se, as a product, tool, and entity in its own right. Finally, this thesis brings to the fore how the female body is constructed within the organisational domain when it is not reproducing. By doing so, it expands our knowledge and balances our discussions as to how the female body is understood when non-reproductive or infertile. The thesis is based on a qualitative study of organisations within the field of fertility treatment in the UK, and entails the critical discourse analysis of organisational texts collected at the Fertility Show, here understood as a FCE. The study critically investigates how organisations discursively construct the female non-reproductive body; which relations they put in place between themselves and the bodies they construct; and how such bodies and relations discursively maintain the field’s legitimacy at the FCE. The analysis shows that organisations at the Fertility Show construct three discourses of the female non-reproductive body, and that each discourse engenders an imbalanced relation between the organisations and the female body. It further shows that each discourse and relation is rooted in past discourses on womanhood and motherhood, which are not explicitly employed by organisations at the FCE. Further, the research illustrates that, in this setting, organisations maintain field legitimacy through the discursive strategies of adaptation to social norms, reiteration of past discourses, and temporary interruption of social norms. At the FCE, legitimacy is thus sustained by adapting to current social norms on motherhood; by reiterating broader historical discourses on the female body; and by temporarily interrupting the current social norm that views infertility as taboo. Building on the term ‘discursive space’ from Hardy and Maguire (2010), the study further contributes to our knowledge of discourse and FCEs by showing that FCEs can be approached as open discursive spaces where imbalanced relations are generated through discourse. It illustrates that FCEs are open spaces because, while they are temporally and spatially bounded, the discourses employed therein are not. The analysis shows that past discourses are employed at the FCE to maintain legitimacy, but not explicitly so. This in turn makes resistance hard to carry out. The study further contributes to how we methodologically approach FCEs by applying a CDA approach to the study of discourse within FCEs. Particularly, a CDA approach explicitly shows that discourse can foster legitimacy through the creation of imbalanced relations between text producers and text consumers. This in turn brings to the fore issues of power, struggle, and resistance within and outside of the FCE. With respect to organisation studies centred on the female body and reproduction, the thesis highlights how fertile bodies and infertile bodies exist in a dualistic system of societal and organisational expectations that cannot be simultaneously satisfied. Consequently, the female body finds itself locked in a lose-lose situation with regards to its reproductive choices, within and outside of organisational life.